The Integration of Facebook to Make Teaching and Learning Writing Skill in EFL More Entertaining - Dita Amelia Rosang (Indonesian Journal Of Educational Research and Review, 2021)
The students as EFL learners have difficulty in improving their writing skills. Students are less enthusiastic in compiling their writings, and they also have difficulty in it. Several factors, such as students cause this are less interested in English and less understanding vocabulary and grammar. This study analyzes that Facebook can be used as a more entertaining way of teaching and learning EFL writing skills. This research is library research. This study collects data by analyzing data information. Social networking sites (SNS) in this study use Facebook. The results showed that Facebook was able to encourage student participation and achievement in language learning. There are several steps in implementing Facebook as a more entertaining way of learning to teach EFL writing skills, such as having a Facebook account, online classes on Facebook, assignments or assignments on Facebook, sharing ideas, and feedback. Thus, the application of Facebook as a more entertaining way of learning EFL writing skills gives positive results to students' academic achievement.